2013
DOI: 10.1364/oe.21.023241
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement distribution over 300 km of fiber

Abstract: Abstract:We report the distribution of time-bin entangled photon pairs over 300 km of optical fiber. We realized this by using a high-speed and high signal-to-noise ratio entanglement generation/evaluation setup that consists of periodically poled lithium niobate waveguides and superconducting single photon detectors. The observed two-photon interference fringes exhibited a visibility of 84 %. We confirmed the violation of Bell's inequality by 2.9 standard deviations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
131
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(132 citation statements)
references
References 32 publications
1
131
0
Order By: Relevance
“…However, this method is known to be sensitive to polarization mode dispersion in optical fibers [11]. As an alternative, entanglement in the time-energy basis may be employed, wherein quantum information is encoded in the arrival time of photons, and long-distance fiber transmission over 300 km is possible [12]. The approach of using time-energy entangled photons was first formulated by Franson, with photon pairs created in an atomic decay process and two unbalanced interferometers [13].…”
mentioning
confidence: 99%
“…However, this method is known to be sensitive to polarization mode dispersion in optical fibers [11]. As an alternative, entanglement in the time-energy basis may be employed, wherein quantum information is encoded in the arrival time of photons, and long-distance fiber transmission over 300 km is possible [12]. The approach of using time-energy entangled photons was first formulated by Franson, with photon pairs created in an atomic decay process and two unbalanced interferometers [13].…”
mentioning
confidence: 99%
“…In order to realize quantum communication system, a long-distance entanglement distribution is also important, and recently experiments of an entanglement distribution over 300 km of the optical fiber has been achieved by using SSPDs [45]. Very recently, a new scheme named the measurement-device-independent QKD (MDI-QKD) protocol, in which the security never relies on the measurement, has been actively studied, and high-performance SSPDs were implemented also in the MDI-QKD systems as a key device [46].…”
Section: Quantum Communicationmentioning
confidence: 99%
“…It has been suggested that a design by Franson [23] could be used to achieve the same unconditional security as traditional QKD protocols. Several experiments have evaluated this Franson-type setup [24][25][26][27][28][29][30][31], however this thesis will show that there are complications when basing QKD on energy-time phenomena.…”
Section: Cryptography and The Quantum Worldmentioning
confidence: 99%
“…Using the Franson interferometer we can also perform QKD to generate a secret key and this has also been tested experimentally QKD [24][25][26][27][28][29][30][31]. Keep in mind, however, that the Franson setup uses a postselection step.…”
Section: The Franson Interferometermentioning
confidence: 99%